Applying the Community of Inquiry Framework to an Online Professional Practice Doctoral Program - Kumar, Swapna; Dawson, Kara; Black, Erik W.; Cavanaugh, Catherine; Sessums, Christopher D. (International Review of Research in Open and Distributed Learning, 2011)
The community of inquiry (CoI) framework has commonly been used to study teaching and learning in online courses (Garrison, Anderson, & Archer 2000). This paper describes the implementation of the CoI framework in a cohort-based online EdD program, where teaching presence and cognitive presence were easier to foster than social presence. Based on the results of an initial evaluation, suggestions are made to expand the components of the CoI framework when using it at a program level. Lessons learned from the implementation are also shared to assist others wishing to apply the CoI framework to online graduate programs.